“Gestão de riscos: avaliação de riscos operacionais em uma empresa de serviço de entrega de encomendas” - SANTOS, Aldo César Cruz dos (2017)
The risk management is a growing interest subject in the academic environment as well as in the business world. The theoretical approaches of the theme “risk” had begun and evolved in the economic sciences, however, being aware of the advantages of the risk management activity, including to attract the investors attention, the non-financial corporations have been trying to adjust techniques and tools developed to the reality of the financial sector. Based in the risk management model proposed in NBR ISO 31000: Gestão de Riscos - Princípios e diretrizes(ABNT) which origin is the ISO 31000: Risk management - Principles and guidelines, this work approaches the risks assessment in the reality of a transportation and small parcel delivery services company. The research has an exploratory feature and it uses the beta regression analysis method to identify the operational risk factors that explains the failures of the company in delivering until the deadline. Based in the data taken in the company, two econometric models are created and their results indicate that problems in the air transport, employees strikes and deliverers robberies, for example, they are significant variables in the cause of delays. Recommendations about the possible actions that have to be contemplated in the risk treatment plan are driven to the company, considering the phases of the risk management process, respecting the limitations of the models in respect of their capacity of explain the phenomenon. The practice does not only demonstrate the possibility of risk assessment with scientific criteria and safety, but it also seems to be efficient in deepening the knowledge about the risk, thanks to the analysis that had been made. Therefore, the risk treatment becomes more effective, focusing on the significant factors in order to eliminate the risks or reduce them to acceptable levels.